Answer:
They will always intersect at one point
Step-by-step explanation:
^^
Answer:
Step-by-step explanation:
15+10y−4xy−66
Soustraire 66 de 15 pour obtenir −51.
−51+10y−4xy
The apple is cut into 10 pieces so each piece is 1/10 of the apple. 1/10=.1; .8=8/10 so 8 pieces are eaten. 2 pieces are left which is 2/10 of the apple which simplifies to 1/5 because 2 and 10 are both divisible by 2. 2 divided by itself is 1 and 10 divided by 2 is 5. So the amount of the apple left in simplest form of a fraction is 1/5.
Answer:
10000π units²
Step-by-step explanation:
From the question given above, the following data were obtained:
Circumference (C) = 100π
Surface Area of sphere (SA) =?
Next, we shall determine the radius. This can be obtained as follow:
Circumference (C) = 100π
Radius (r) =?
C = 2πr
100π = 2πr
Divide both side by 2π
r = 100π / 2π
r = 50 units
Finally, we shall determine the surface area of the sphere. This can be obtained as follow:
Radius (r) = 50 units
Surface Area of sphere (SA) =?
SA = 4πr²
SA = 4 × π × 50²
SA = 4 × π × 2500
SA = 10000π units²
Therefore, the surface area of the sphere is 10000π units²
Answer:
A. √3 : 2
D. 3√3 : 6
Step-by-step explanation:
In a triangle described as 30°-60°-90° triangle, the base angles are 90° and 60°
The side with angles 90° and 60° is the shortest leg and can be represented by 1 unit
The hypotenuse side is assigned a value twice the shorter leg value, which is 2 units
From Pythagorean relationship; the square of the hypotenuse side subtract the square of the shorter leg gives the square of the longer side
This is to say if;
The given the shorter leg = 1 unit
The hypotenuse is twice the shorter leg= 2 units
The longer leg is square-root of the difference between the square of the hypotenuse and that of the shorter leg
![=2^2-1^2\\\\=4-1=3\\\\\\b^2=3\\\\\\b=\sqrt{3}](https://tex.z-dn.net/?f=%3D2%5E2-1%5E2%5C%5C%5C%5C%3D4-1%3D3%5C%5C%5C%5C%5C%5Cb%5E2%3D3%5C%5C%5C%5C%5C%5Cb%3D%5Csqrt%7B3%7D)
where the longer leg is represented by side b in the Pythagorean theorem, the hypotenuse by c and the shorter leg by a to make;
![a^2+b^2=c^2](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2%3Dc%5E2)
<u>Hence the summary is</u>
a=shorter leg= 1 unit
b=longer leg = √3 units
c=hypotenuse=2 units
The ratio of longer leg to its hypotenuse is
=√3:2⇒ answer option A
This is the same as 3√3:6 ⇒answer option D because you can divide both sides of the ratio expression by 3 and get option A
![=3\sqrt{3} :6\\\\\\\frac{3\sqrt{3} }{3} :\frac{6}{3} \\\\\\=\sqrt{3} :2](https://tex.z-dn.net/?f=%3D3%5Csqrt%7B3%7D%20%3A6%5C%5C%5C%5C%5C%5C%5Cfrac%7B3%5Csqrt%7B3%7D%20%7D%7B3%7D%20%3A%5Cfrac%7B6%7D%7B3%7D%20%5C%5C%5C%5C%5C%5C%3D%5Csqrt%7B3%7D%20%3A2)
Answers are :option A and D